Au/PAr/n-CdS/ITO polymer insulated MIS structure - Caliskan, M.; Kuruoglu, F.; Serin, M. (NATL INST OPTOELECTRONICS, 2014)
In this work, we present optical, structural and electrical characterizations of Au/PAr/CdS metal interlayer semiconductor diode (MIS) structure by X-Ray diffraction (XRD), ultraviolet-visible (UV-vis) spectroscopy and curent-voltage (I-V) measurements at room temperature and in the dark. CdS was deposited onto ITO substrates by spray pyrolysing method, PAr was coated over CdS by drop-casting method and a gold metal contact was evaporated by e-beam evaporation system. The barrier height of Au/CdS (MS) structure was calculated to be 0,48eV. The barrier height of Au/PAr/CdS MIS structure was found different from that of the SBH value of Au/CdS MS structure. For the Au/PAr/CdS (MIS) structure, the barrier height, phi(B), and ideality factor, n, have been calculated as 0.61 eV and 2,25, respectively, from forward bias I-V measurements. The higher ideality factor attributed to the series resistance, R-s was calculated as 907.4 k Omega and 897.1 k Omega from Cheung functions. The effective barrier height, phi(B), and the series resistance, R-s, of the Au/PAr/CdS structure were also calculated using Norde method and found to be as 0.74 eV. and 974 k Omega respectively. The interface state density (N-ss) were obtained from the forward bias I-V characteristics at a region changing from 4x10(15) eV(-1)cm(-2) to 1x10(15) eV(-1)cm(-2). The charge transport mechanism of the structure were determined by the power law behaviour of the current with different exponent I proportional to Vm+1 were determined and three main slopes were found.
Keywords: Au/PAr/CdS; Schottky diode; MIS structure parameters; Density of states; Charge transport mechanism; CURRENT-VOLTAGE CHARACTERISTICS; ELECTRICAL CHARACTERISTICS; SERIES RESISTANCE; THIN-FILMS; TRANSPORT-PROPERTIES; NONVOLATILE MEMORY; BARRIER HEIGHT; LAYER; PERFORMANCE; Materials Science; Optics; Physics